The The Relationship Between Healthcare Professionals' Interprofessional Competence and Response Speed in Acute Emergencies: The Relationship Between Healthcare Professionals' Interprofessional Competence and Response Speed in Acute Emergencies - Hatta, Rezky Darmawan (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Acute emergencies are medical conditions that require rapid and appropriate treatment to prevent death or further damage to the patient. This situation often involves various health workers with different expertise, ranging from doctors, nurses, nutritionists, pharmacists, to other medical personnel. In dealing with acute emergency cases, one of the factors that determine the success of the treatment is the speed of action taken by the medical team. This speed depends not only on individual abilities, but also on how various health workers can collaborate effectively in a team. Interprofessional competence, which refers to the ability of health workers from different professions to work together to provide optimal health care, plays a very important role in such situations. Effective communication, a clear understanding of each team member's role, and collaboration skills are key elements that influence how quickly and appropriately the medical team can take the necessary actions in an emergency. The results of this study indicate that there is a significant relationship between interprofessional competence and team collaboration with the relationship between experience and competence there is a significant relationship between interprofessional competence and team collaboration with the relationship between experience and competence with a significant value of p = 0.001 < 0.05.